Employee Engagement Dan Millenials Indonesia - Aris Setiyani (Jurnal Doktor Manajemen (JDM), 2019)
In this era of global change, where the millennial generation has begun to enter the workforce, more and more workers around the world are feeling uneasy about staying in their current jobs. Even in a survey conducted  by TNS Employee Insights, a survey agency in the United States, stated that only 14.3% of workers were fully engaged with the company, 29.7% were involved and the rest did not want to be involved in the organization. The survey also noted about 45% of respondents who stated they were not satisfied with their work. The level of employee dissatisfaction will negatively affect the behavior and feelings of employees in a company. This study aims to look at the 3 variables, namely compensation, flexible working hour  and company branding, which is the most influential on employee engagement to stay and  be involved in realizing the ideals of the organization. This research was conducted on millennial respondents who had worked for at least 1 year  in various industries both manufacturing and service industries in the area of West Java, Central Java and East Java as well as Jabodetabek, Indonesia. The number of samples collected and calculated were 285 respondents. Data calculation is done using SEM-AMOS software. From the analysis of the data it was found that compensation, flexible working hour  and company branding  have an influence on employee motivation and employee engagement, and employee motivation has the effect of mediating the relationship between compensation, flexible working hour and company branding on employee  engagement.